Hand grip strength and quality of life in older adults practicing Pilates method exercises: A cross-sectional study - Amanda Tami Colevate; José Roberto Nascimento Júnior; Eduardo Silva; Priscila Ester de Lima Cruz; Daniel Vicentini de Oliveira (Journal of Physical Education (Maringá), 2025)
This cross-sectional study assessed the quality of life and hand grip strength in 71 older adults practicing Pilates method exercises. The WHOQOL-Bref, WHOQOL-Old, and handgrip dynamometer tests were utilized. Data were analyzed using the Kolmogorov-Smirnov test, skewness and kurtosis coefficients, bootstrap procedure, Pearson correlation, and t-test (p < 0.05). No significant correlations (p > 0.05) were found between handgrip strength and the domains and facets of quality of life. However, positive and significant correlations (p < 0.05) were observed among the domains and aspects of quality of life. There was no significant difference (p > 0.05) in comparing the quality of life domains and facets among older adults practicing Pilates based on the degree of handgrip strength. Although handgrip strength did not show significant correlations with the various domains and aspects of quality of life in older individuals practicing Pilates, positive associations were observed among these different aspects.